Предмет: Алгебра, автор: maximrepenko123

умоляю помогите очень надо!​

Приложения:

Ответы

Автор ответа: MagdaSinger
0

Ответ:

7m(m  ^ { 3  }  -8m  ^ { 2  }  +9) =7m ^4-56m ^3 +63m\\ (x-2)(2x+3) =2x ^2+3x-4x-6=2x ^2-x-6\\ (3m-4n)(5m+8n) =15m ^2+24mn-20mn-32n ^2=15m ^2 +4mn-32n ^2\\ ( y+3) (  { y  }^{ 2  }  +y-6)   =y ^3+4y ^2-3y-18

12ab-18b  ^ { 2  }   =6b(2a-3b)\\ 21x  ^ { 7  }  -7x  ^ { 4  }   =7x ^4 (3x ^3-1)\\ 8x-8y+ax-ay =(a+8)(x-y)\\

2c(3c-7)-(c-1)(c+4) =6c ^2-14c-(c-1)(c+4)=6c ^2-14c-c ^2-3c+4=5c ^2-17c+4

\dfrac{ 4x-1  }{ 9  }  - \dfrac{ x+2  }{ 6  }  =2  |*18\\2(4x-1)-3(x+2)=36\\8x-2-3x-6=36\\5x-8=36\\5x=44\\x=\dfrac{44}{5} =8\dfrac{4}{5}

(3x-5)(2x+7)=(3x+1)(2x-3)+4x \\6x ^2+11x-35=(3x+1)(2x-3)+4x\\6x ^2+11x-35=6x ^2-7x-3+4x\\11x-35=-3x-3\\14x-35=-3\\14x=32\\x=\dfrac{32}{14} \\x=2\dfrac{2}{7}

14xy-2y+7x-1 =(7x-1)(2y+1)\\ (7 *  \dfrac{ 8  }{ 7  }  -1)( 2*(- \dfrac{ 6  }{ 10  }  )+1)   =7*((-\dfrac{6}{5} )+1)=7(-\dfrac{6}{5} +\dfrac{5}{5})=7*-\dfrac{1}{5}=-\dfrac{7}{5}=-1\dfrac{2}{5}

81  ^ { 5  }  -27  ^ { 6  }   = (3  ^ { 4  }  )  ^ { 5  }  -(3  ^ { 3  }  )  ^ { 6  }  =3  ^ { 20  }  -3  ^ { 18  }  =3  ^ { 18  }  (3  ^ { 2  }  -1)=3  ^ { 18  }  (9-1)=3  ^ { 18  }  *  8

x  ^ { 2  }  -12x+20 \\\sqrt{D} =\sqrt{144-4*1*20} =8\\x_{1} =\dfrac{12-8}{2} =2\\x_{2} =\dfrac{12+8}{2} =10\\ x  ^ { 2  }  -12x+20=(x-10)(x-2)

Объяснение:

Похожие вопросы
Предмет: Русский язык, автор: iskakovaaaaaaa